Zawód korespondenta – misja czy powołanie? - Działak-Jankowska, Julita (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2018)
A reporter should look and behave in an ordinary, average way, and should not stand out from the crowd. Then it is easier for him or her to blend in, to not draw attention to themselves, to not stand out or attract anybody’s attention with his or her looks and behavior. One talks to a journalist in a different way than to somebody one has met by chance. Therefore, a reporter should be anonymous and unknown. He or she should be like anyone from the crowd. If reporters lose their anonymity, they also lose an opportunity to write a good reportage. Ryszard Kapuœciñski observed that the profession of a reporter is about overcoming your own feeling of being different – about living in an African or Chinese village, or some place in Latin America, among the Indians in the Andes. A good correspondent needs to identify himself or herself with these people, their way of living, their poverty and difficulties. It is a condition of any work to overcome ‘the Other’ in oneself.
The Profession of a Correspondent - a Mission or a Vocation?